2023
DOI: 10.1038/s41598-023-36410-y
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression and clinical significance of TBX15 in human gliomas

Abstract: T-box transcription factor 15 (TBX15) is upregulated in a variety of tumors and has been reported to promote uncontrolled proliferation of tumor cells and induce tumor cells to avoid apoptosis, thus accelerating the malignant transformation of malignant tumors. However, the prognostic value of TBX15 in glioma and its relationship with immune infiltration remain unknown. In this study, we intended to explore the prognostic value of TBX15 and its link to glioma immune infiltration and examine TBX15 expression in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
1
0
2
Order By: Relevance
“… 24 There is a study showed that TBX15 was upregulated in glioma tissues and indicated poor prognosis of glioma patients. 25 Results of our study on gliomas was consistent with these studies. In addition, knocking down TBX15 in glioma cells repressed their proliferation, migration and invasion rates, along with their ability to polarize macrophages to the M2 phenotype.…”
Section: Discussionsupporting
confidence: 90%
“… 24 There is a study showed that TBX15 was upregulated in glioma tissues and indicated poor prognosis of glioma patients. 25 Results of our study on gliomas was consistent with these studies. In addition, knocking down TBX15 in glioma cells repressed their proliferation, migration and invasion rates, along with their ability to polarize macrophages to the M2 phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is known that recurrent GBMs are highly immunosuppressive [ 68 ]. TBX15 was suggested to be associated with immune cell infiltration and immunosuppression and exhibit poor clinicopathological characteristics and survival prognosis in glioma patients [ 69 ]. For the remaining signatures ( TAS2R1 , CDKL1 , and CD101 ), the relevance of them to GBM recurrence is still greatly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Ген TBX15 принадлежит к семейству генов T-box. Фактор транскрипции TBX15 активируется в различных опухолях и способствует неконтролируемой пролиферации опухолевых клеток, помогая избегать апоптоз [38]. Экспрессия TBX15 увеличена в глиомах человека и ассоциируется с ухудшением выживаемости пациентов с данной патологией.…”
Section: матричная рнкunclassified
“…Экспрессия TBX15 увеличена в глиомах человека и ассоциируется с ухудшением выживаемости пациентов с данной патологией. Кроме того, повышенная экспрессия TBX15 связана с генами, участвующими в иммуносупрессии при глиоме [38].…”
Section: матричная рнкunclassified